PERBEDAAN TEKANAN AIR PADA MEMBRAN REVERSE OSMOSIS TERHADAP PENURUNAN JUMLAH BAKTERI ESCHERICHIA COLI PADA AIR BERSIH DI INDUSTRI TEKSTIL (Jurnal Kesehatan Siliwangi, 2021)
Water is very useful for household, industrial, and other public places. The use of clean water in the textile industy used for washing tableware and food processing. The results of clean water used contained 41 APM/100 ml of Escherichia coli bacteria. The clean water did not meet the criteria because it exceeds the regulated threshold value, so it is necessary to treat clean water using Reverse Osmosis (RO) membrane technology. The purpose of this research was to determine the difference in the number of Escherichia coli bacteria with various variations in water pressure after being treated with RO membrane. This research used water pressure of 2 bar, 2.5 bar and 3 bar. This research was an experimental research with the research design used pre test post test without control, the sampling technique used grab sampling. Analysis of the decrease in the number of Escherichia coli bacteria was carried out descriptively. The water pressure used was able to reduce Escherichia coli bacteria to 0 APM/100 ml, this can happen because the pores of the RO membrane were smaller than the size of Escherichia coli bacteria. The conclusion in this research was there was a difference in the variation of pressure used on the RO membrane to decreased the number of Escherichia coli bacteria. For further research, it is expected to replace the RO membrane every time do the test to avoid saturation conditions on the RO membrane.